Spawning grounds of pacific cod Gadus macrocephalus in the North-West Pacific - Andrei B. Savin (Известия ТИНРО, 2016)
Spatial patterns of the pacific cod spawning grounds in the North-West Pacific are considered in the first time on the basis of its spawners occurrence and distribution of its larvae, fingerlings, and yearlings by samples collected in 179 surveys of Pacific Fish. Res. Center (TINRO) in 1975-2014 and cited data. The spawning grounds are located either at the shelf edge and upper continental slope for offshore forms of cod or on the shallows for its coastal form. The deep-water spawning grounds are related to the areas with shoreward currents that provide the transport of pelagic larvae and fry to the shallows favorable for their further development. They are located, by the regions: in the western Bering Sea - over underwater Shirshov Ridge, southward form Cape Navarin, in the Olyutorsky Bay, eastward from Karaginsky Island, at Commander Islands, in the Kronotsky Bay; at Kamchatka and Kuril Islands - off the northeastern coast of Kamchatka, at the southeastern Kamchatka between 50о50′-52о15′ N, in the Second Kuril Strait, at the Pacific side of Onekotan, Kunashir and possibly Shikotan Islands, in the Kunashir Strait, at the Okhotsk Sea side of Kunashir and Iturup Islands, at the western coast of Kamchatka between 51-56о N; in the northern Okhotsk Sea - along the edge of the northern Okhotsk Sea shelf and possibly somewhere in the Shelikhov Bay; in the Japan Sea - in the De Langle Bay at the western coast of Sakhalin, in the Nevelskoy Bay, at Moneron Island, at northeastern coast of Primorye between 44о27′-48о10′ N, and at the southern Primorye coast. The shallow spawning grounds are poorly known, they are determined definitely in the Tauiskaya Guba Bay (northern Okhotsk Sea) only, but could be expected in other areas, too.